Moderate and severe pharyngitis in young adult inhabitants of Poznan, western Poland - Bura, Maciej; Michalak, Michał; Chojnicki, Michał; Padzik, Magdalena; Mozer-Lisewska, Iwona (Family Medicine & Primary Care Review, 2017)
Background. Acute pharyngitis is a frequent clinical problem. Objectives. To assess: the frequency of streptococcal etiology (β-HS ) in moderate to severe pharyngitis among young adult patients, the accuracy of the Centor score (CS ) in predicting the likelihood of the β-HS etiology and the usefulness of the rapid antigen detection test (RAD T) in the appropriate selection of patients that ought to be treated with antibiotics. Material and methods . 202 individuals (101 patients and a sex- and age-matched control group) aged 18–44 participated in the study. Two throat swabs were performed: the first one to carry out RAD T for group A streptococci (GAS ), and the second one to grow a conventional culture. Data on the antibiotic therapy were recorded as well. Results. β-HS were responsible for one-third of the studied cases of pharyngitis (GAS – 22.8%, 23/101; high non-GAS colony count – 9.9%, 10/101). The frequency of the isolation of β-HS depending upon the CS was as follows: CS 2 – 13.2% (5/36), CS 3 – 40.5% (15/36), CS 4 – 61.5% (16/36). RAD T’s effectiveness in identifying GAS was significantly higher than that of CS alone (p < 0.001). Antibiotics were prescribed in 59 cases, including 45% of RAD T-negative patients (35/77). The primary choice was penicillin (37.3%, 22/59). Conclusions . In young adult pharyngitis patients with CS 2-4, β-HS are responsible for a minority of cases. Among these bacteria, almost one third are non-GAS . Centor criteria, as the only diagnostic tool in predicting the streptococcal etiology of the disease, are of moderate usefulness. The use of RAD T significantly increases the diagnostic accuracy of GAS –related pharyngitis.